Penerimaan Pengguna E-Wallet Menggunakan UTAUT 2 (Studi Kasus) - Muhammad Taufik Hidayat; Qurrotul Aini; Elvi Fetrina (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2020)
Nowadays, e-wallet (electronic wallet) is used for non-cash transactions because of the ease and practicality of transactions offered by service providers in South Tangerang. However, the success of the server-based e-wallet that has been implemented is still unknown, and there are still problems in the form of loss of balance and failure to top up. One of determinants of the system to be successful is in terms of user acceptance perspective. The objective of this paper is to derive and investigate significant variables on the user acceptance of server-based e-wallets in South Tangerang with the UTAUT 2 model and the addition of two variables, namely perceived trust and perceived risk. The study is conducted with a quantitative approach, questionnaires online with 33 questions, and demographic data analysis using IBM SPSS 25, as well as PLS-SEM analysis using SmartPLS 3.2.8. The results show that out of twelve proposed hypotheses, three hypotheses are declared insignificant and rejected because the path coefficient value and t-test of these hypotheses (performance expectancy, hedonic motivation, and price value) are less than 0.1 and 1.96. In contrast, nine others are declared significant and accepted.